AKIN10 and FUSCA3 interact to control lateral organ development and phase transitions in Arabidopsis - Tsai, Allen Yi‐Lun; Gazzarrini, Sonia (The Plant journal : for cell and molecular biology, 2012)
Summary The Snf1 (sucrose non‐fermenting‐1)/AMPK (AMP‐activated protein kinase)/SnRK1 (Snf1‐related protein kinase 1) kinases act as sensors of energy status in eukaryotes. Despite the important role of these kinases in regulation of cellular responses to metabolic stress, only a few SnRK1 substrates have been identified. Using yeast two‐hybrid screens, we isolated AKIN10 as an interactor of the B3‐domain transcription factor FUSCA3 (FUS3), an essential regulator of seed maturation in Arabidopsis. Pull‐down and bi‐molecular fluorescence complementation (BiFC) assays confirm the interaction in vitro and in planta, respectively. In‐gel kinase assays show that AKIN10 phosphorylates FUS3 and that the N‐terminal domain of FUS3 is required for AKIN10 phosphorylation. Mutations of three serines (fus3S55A/S56A/S57A) within a partial SnRK1 consensus sequence in the N‐terminal region of FUS3 reduce greatly FUS3 phosphorylation by AKIN10, which indicates that these serines are the predominant AKIN10 target sites. In a cell‐free system, AKIN10 positively regulates FUS3 stability, as overexpression of AKIN10 delayed the degradation of the recombinant FUS3. Plants over‐expressing AKIN10 show delayed seed germination, vegetative growth and flowering time, indicating that AKIN10 antagonizes the embryonic‐to‐vegetative and vegetative‐to‐reproductive phase transitions. Furthermore, overexpression of AKIN10 alters cotyledon, silique and floral organ development, suggesting that AKIN10 regulates lateral organ development. Genetic interaction studies show that the fus3‐3 mutation partially rescues the phase transition and organ development defects caused by AKIN10 overexpression. Taken together, these findings indicate that FUS3 and AKIN10 interact physically and share overlapping pathways to regulate developmental phase transitions and organogenesis in Arabidopsis.